Descending the Mountain: Exploring the Impact of Research on Pedagogy and Practice - Jana Baumgaertner (Bern Open Publishing, 2021)
Conference Report to the virtual Scientific conference of the International Association for Physical Education in Higher Education (AIESEP) 2021 hosted by the University of Alberta and McGill University (Banff, Canada).